2019
DOI: 10.1111/odi.13094
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of hsa_circ_0072387 as a valuable predictor for oral squamous cell carcinoma

Abstract: Objective Increasing evidence points toward the key function of circular RNAs (circRNAs) in various carcinomas. This study aimed to identify aberrant expression of hsa_circ_0072387 in oral squamous cell carcinoma and probe its clinical significance. Materials and Methods Real‐time quantitative reverse transcription–polymerase chain reaction (qRT‐PCR) was used to assess hsa_circ_0072387 expression levels in 63 paired OSCC tissues and three OSCC cell lines. The area under the receiver operator characteristic (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Nevertheless, to the best of our knowledge, only 1 study, reported by Wang et al [20], analyzed the profiles of differentially-expressed circRNAs in OSCC patients. In addition, fewer than 20 articles have demonstrated that circRNA is related to the progression of OSCC [46][47][48][49][50][51][52][53]. For instance, Wang et al reported that circDOCK1 can inhibit OSCC cell apoptosis by regulating BIRC3 expression [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, to the best of our knowledge, only 1 study, reported by Wang et al [20], analyzed the profiles of differentially-expressed circRNAs in OSCC patients. In addition, fewer than 20 articles have demonstrated that circRNA is related to the progression of OSCC [46][47][48][49][50][51][52][53]. For instance, Wang et al reported that circDOCK1 can inhibit OSCC cell apoptosis by regulating BIRC3 expression [46].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al reported that circDOCK1 can inhibit OSCC cell apoptosis by regulating BIRC3 expression [46]. Dou et al discovered hsa_circ_0072387 expression was reduced in OSCC samples and was related to the TNM stage in OSCC [51]. Sun et al found hsa_circ_001242 expression in OSCC was substantially downregulated compared to AHTs [52].…”
Section: Discussionmentioning
confidence: 99%
“…Su et al 17 postulated that hsa_circ_0055538 participated in OSCC progression via the p53 signaling pathway, and may thus be a prospective diagnostic biomarker. Similarly, Dou et al 18 suggested that decreased expression of the key circRNA hsa_circ_0072387 in OSCC could make it a potential diagnostic biomarker and therapeutic target in OSCC. Furthermore, Zhu et al 19 revealed that the hsa_circRNA_100533-miR-933-guanine nucleotide-binding protein axis affected the biological behavior of OSCC cells via a mechanism of competing endogenous RNAs (ceRNAs), suggesting that hsa_circRNA_100533 may also be a novel diagnostic biomarker and therapeutic target for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-145 and miR-29 are both tumor suppressor genes in OSCC. Shao et al found that miR-145 inhibited the growth of OSCC cells by targeting c-Myc and CDK6 27 , while miR-29-3p was also a predicted target of circ_0072387 in oral squamous cell carcinoma cells 28 . Further analysis revealed that miR-145-5p and miR-29b-3p could jointly target CPEB3, PAN2, RLIM, NEXMIF, CFL2 and PHACTR2.…”
Section: Discussionmentioning
confidence: 99%